2015
DOI: 10.1007/s13277-015-3075-1
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-15a induces cell apoptosis and inhibits metastasis by targeting BCL2L2 in non-small cell lung cancer

Abstract: MicroRNAs (miRNAs) play a critical role in cancer development and progression. Aberrant expression of miR-15a has recently been reported in several cancers, but its role in non-small cell lung cancer (NSCLC) still remains obscure. We investigated the effects of miR-15a on proliferation, apoptosis, and metastasis in A549 cells. Eighteen paired NSCLC and adjacent non-tumor lung tissues were surgically removed and immediately snap frozen until total RNA was extracted and confirmed by two independent pathologists.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 20 publications
0
36
1
1
Order By: Relevance
“…Furthermore, our data revealed that a transcriptionally competent MYC was required for the reduction in BCL-W expression. However, there was no evidence of direct transcriptional activation by MYC, suggesting that MYC was indirectly regulating the expression of BCL-W. We (here) and others (27)(28)(29) have shown that Bcl-w is a target of the miR-15 family, which is known to be regulated by MYC (40). In addition, we recently demonstrated that MYC downregulates the expression of BCL-2 and BCL-XL by transcriptionally upregulating the levels of the miR-15 and let-7 families, respectively (22,23).…”
Section: Bcl-w Overexpression In Diffuse Large B Cell Lymphoma Correlmentioning
confidence: 57%
See 1 more Smart Citation
“…Furthermore, our data revealed that a transcriptionally competent MYC was required for the reduction in BCL-W expression. However, there was no evidence of direct transcriptional activation by MYC, suggesting that MYC was indirectly regulating the expression of BCL-W. We (here) and others (27)(28)(29) have shown that Bcl-w is a target of the miR-15 family, which is known to be regulated by MYC (40). In addition, we recently demonstrated that MYC downregulates the expression of BCL-2 and BCL-XL by transcriptionally upregulating the levels of the miR-15 and let-7 families, respectively (22,23).…”
Section: Bcl-w Overexpression In Diffuse Large B Cell Lymphoma Correlmentioning
confidence: 57%
“…Therefore, we postulated that MYC may be indirectly altering Bcl-w expression through miR. As we (Supplemental Figure 7) and others (27)(28)(29) have shown, Bcl-w mRNA is targeted and negatively regulated by the miR-15 family. Recently, we reported that MYC transcriptionally upregulates this miR family as a mechanism to downregulate Bcl-2 expression (22,23).…”
Section: Bcl-w Expression Is Modulated By the Myc-regulated Mir-15 Famentioning
confidence: 63%
“…The expression of specific miRNAs may be upregulated in particular types of cancer and downregulated in others; this conflicting observation is predominantly a result of differences in the mechanisms of oncogenesis between tumor types (22,23). Upregulated miRNAs in cancer act as oncogenes by negatively regulating tumor suppressor genes, whereas downregulated miRNAs act as tumor suppressors via the blockade of oncogenes in tumor progression (24,25). Therefore, identifying the targets of miRNAs is essential for understanding the functions of miRNAs in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, EGCG-regulated miRNAs targeted FOXO1, BCL2L1, BCL2L2, PTEN, BBC3, and MDM2 which are the regulator genes against cell growth, proliferation, and cell death. When FOXO1 is overexpressed, cell proliferation and growth is inhibited by upregulating caspase-3 and caspase-9 and inducing G2/M arrest and (Yang et al 2015). BCL2L1 and BCL2L2, BCL2 family, are pro-oncogene and repress intrinsic pathwaymediated cell death (Denoyelle et al 2014;Zhang et al 2015).…”
Section: Discussionmentioning
confidence: 99%